Cost Savings of Carpal Tunnel Release Performed In-Clinic Compared to an Ambulatory Surgery Center: Time-Driven Activity-Based-Costing. (November 2021) - White, Melissa; Parikh, Harsh R.; Wise, Kelsey L.; Vang, Sandy; Ward, Christina M.; Cunningham, Brian P.
Purpose: The purpose of our study was to investigate carpal tunnel release (CTR) performed in the clinic versus the ambulatory surgery center (ASC) to evaluate for potential cost savings.Methods: Patients who underwent either CTR in clinic under a local anesthetic or CTR in the ASC with sedation and local anesthetic were prospectively enrolled in a registry between 2014 and 2016. All patients completed a Visual Analog Scale (VAS) pain scale for procedural and postprocedure pain. Time-Driven Activity-Based Costing (TDABC) was utilized to quantify cost of both CTR in clinic and CTR in the ASC. Statistical analysis involved parametric comparative tests between patient cohorts for both the TDABC-cost and patient pain.Results: A total of 59 participants completed the postprocedure CTR survey during the study period, 23 (38.9%) in the ASC group and 36 (61.1%) in the clinic group. Overall time for the procedure from patient arrival to discharge was significantly longer for the ASC cases, averaging 215.7 minutes (range: 201-230) compared to 78.6 minutes (range: 59-98) in the clinic group ( P < .01). Both procedural and postoperative VAS pain scores were comparable between clinic and ASC cohorts, procedural pain: 1.8 vs 1.9 ( P = .91) and postoperative pain: 4.8 vs 4.9 ( P = .88). TDABC analysis estimated ASC CTR procedures to cost an average of $557.07 ($522.06-$592.08) and clinic procedures to cost an average of $151.92 ($142.59-$161.25) ( P < .05).Conclusions: CTR in the clinic setting results in significant cost savings compared to CTR in the ASC with no difference in pain scores during the procedure or postoperative period.Level of Evidence: Therapeutic Level II.